Potential scenario of sustainable tourism through women's empowerment: A SMIC-Prob scenario analysis for Penglipuran Village, Bali, Indonesia - Putri, I Gusti Ayu Mira Ananda; Saskara, Ida Ayu Nyoman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
Penglipuran Village is a popular destination for tourists seeking to experience the essence of Bali. Known for its environmentally friendly settlement, Penglipuran is distinguished by its orderly and symmetrical buildings, each with a uniform main gate called Angkul-Angkul. The community places great value on upholding the honor of women in Bali. The objective of this research is to evaluate the potential scenarios that could empower women in the tourism industry and determine the sensitivity of scenarios that drive tourism sustainability in Penglipuran Village. This was achieved using the SMIC-Prob Expert model. The analysis identified three main priority scenarios: (1) working as usual, (2) improving side businesses, and (3) changing the profession. The results indicate that the scenario combination with the highest probability is "110," with an opportunity size of 0.138. This combination, where women continue to work as usual (PrimJob) and focus on the improvement of side businesses (SidePrim), is the best option for women tourism actors to support the sustainability of tourism in Penglipuran Village. Sensitivity analysis, measured by elasticity, identifies SidePrim as the "prime mover" or main driver of tourism sustainability. By implementing improvements in side businesses, women’s involvement in tourism can significantly contribute to achieving future goals alongside stakeholders and the government.